Sistema de gestión de activos fijos tangibles del instituto de suelos de Granma - Naranjo Gallo, Marco Vinicio (2013)
In the Department of Economy of the Institute of Floors of Granma the control of the fixed tangible assets is taken with those that it counts the institution, all the information corresponding to the same ones it was taken in a manual way and by means of Microsoft Excel, that which caused that the information was dispersed, was required of a great number of hours to be upgraded, it was sensitive to losses and deterioration. For that outlined previously, it is that in the present investigation a system of environment web is developed with new potentialities, to facilitate the management from the concerning information to the fixed tangible assets of the Institute of Floors of Granma, allowing a bigger consistency and security of the stored information, facilitating the handling and the quick access to the same one. In this document it is exposed the theoretical foundation, the used tools, the characteristics of the system, design, implementation and the carried out tests. The development of this work is based on technologies multiplatform; it was made use of programming languages like HTML, JavaScript and PHP, as well as Leaves of Styles (CSS). As servant web the Apache was used and I eat agent of databases MySQL, for create and publish the pages it was appealed Dreamweaver CS5, also as development methodology Extreme Programming (XP).